Nutritional Status among a Group of Preschool Children in Relation to Concentration of Selected Elements in Saliva and Caries Severity (A Comparative Study) - Munther, Shahbaa; Majid, Ali Y (Journal of Baghdad College of Dentistry, 2016)
Background: Nutritional status during childhood is very important for individual development and growth. Nutrition has local and systemic effect on the oral health by affecting dental health and salivary composition. This study was aimed to determine effect of iron, sodium and potassium ions in saliva on the nutritional status and to determine the effect of nutritional status on caries severity among preschool children. Material and Methods: The sample consists of 90 children aged 4 and 5 years of both genders, selected from 6 kindergartens in Al-Resafa aspect of Baghdad province. Children classified according to their nutritional status into three groups (normalweight, underweight and overweight). Nutritional status was determined by using body mass index BMI that achieved from height and weight (weight (Kg)/height (m)2). Assessment and recording of caries experience was done by the application of decayed, missing, filled index (dmfs for primary teeth). The diagnosis of dental caries was done according to (d1-4 mfs) criteria for primary teeth. Stimulated saliva was collected from children between 9-11 AM under standardized conditions and chemically analyzed to determine the concentration of iron, sodium and potassium calorimetrically by using ready-made kits and spectrophotometer machine. Data were analyzed using SPSS version 19. Results: Concentration of sodium, potassium and iron ions were (46.64 mg/dl ± 18.00, 31.22 mg/dl ± 9.84, 17.76µg/dl ± 3.17) respectively. From the elements measured in saliva only sodium ions recorded statistically significant difference among the three groups of nutritional status. By application of LSD, the significant difference was found to be between normal weight and overweight groups (46.33 mg/dl ± 17.18, 40.64 mg/dl ± 14.79) respectively (P